ICT Application in Transforming Agricultural Extension Information Service Delivery in Tana River County, Kenya - Gwademba, Goudian; Muthee, Daniel Wambiri; Masinde, Jonson Mulongo (Journal of Information and Knowledge, 2020)
Agricultural Extension includes dissemination of information on farming to farmers in order to help them improve agricultural productivity. A premise exists that if extension programmes are well planned and delivered, they will enhance farming efficiency and output by providing farmers with agricultural information that will help them to utilize their limited production resources. This paper examines how ICT application could help transform public extension service delivery and improve the skills of public agricultural extension service providers and in so doing increase small farmers’ access to agricultural information. This study is set in the Tana River County in Kenya, considered agricultural sector growth and development as vital to the County’s economic stability and community progress. However, while determined efforts in uplifting extension, and firming up their linkage with other actors in agricultural value chains were recognized as important to the future of agricultural development in the county, there is still a lack of evidence of a clear relationship between agricultural productivity and extension services. There was also no clear evidence that small farmers in the county were receiving sufficient extension services to sustainably undertake farming for improved productivity and food safety. While the application of ICTs in agricultural extension was found to be limited, the research acknowledged its important role in facilitating access to agricultural information by providing farmers with timely and relevant agricultural information. The study considered the necessary requirements for setting up an effective agricultural extension information system and it is assumed that this will add credibility to the policy agenda for agricultural extension and communication for rural development.